1,3-Dipolar Cycloaddition in the Preparation of New Fused Heterocyclic Compounds via Thermal Initiation - Porubský, Martin; Tenora, Lukáš; Potáček, Milan (Molecules (Basel, Switzerland), 2016)
This paper describes the synthesis of precursors with a benzo[b]furan skeleton for the intramolecular 1,3-dipolar cycloaddition of azomethine ylides prepared from N-substituted 3-allyl-aminobenzo[b]furan-2-aldehydes and secondary amines derived from α-amino acid esters. Reactions were initiated by heating. The products consisted of four fused rings with three stereogenic centers. Their structure and stereochemistry were determined by NMR spectra and X-ray measurements.
Keywords: fused heterocycles; Cycloaddition Reaction; azosloučeniny; Aldehydes; furany; thiosemikarbazony; Furans; Hot Temperature; molekulární konformace; Azo Compounds; Thiosemicarbazones; 1,3-dipolar cycloaddition; aldehydy; cykloadiční reakce; thermal initiation; 3-amino-benzo[b]furan-2-carbaldehyde; vysoká teplota; Molecular Conformation